Social Innovation: Towards a Better Life after COVID-19 Crisis: What to Concentrate On - Sharafi Farzad, Fatemeh; Salamzadeh, Yashar; Bin Amran, Azlan; Hafezalkotob, Ashkan (Journal of Entrepreneurship, Business and Economics; Vol 8 No 1 (2020), 2020)
We know that saving lives of people is the most important issue during COVID-19 crisis, but we should not forget that due to this crisis, the quality of life for many people will change and new social needs will appear and we must be prepared for that. The main purpose of this research is to find out the areas, which are the most affected ones by the pandemic and have a direct impact on citizens’ lives. This research is a quantitative study, which plans to use the opinions of business and management graduates in Iran to present the status of affected fields of better life index by COVID-19 crisis. A fuzzy TOPSIS method is used here to do this ranking. This research has ranked the most affected indicators of better life index by COVID-19 pandemic. In addition, the profile of this impact including the indicators of better life index and their change is also presented in this research. We found out that most affected indicators are Income, jobs, health, life satisfaction and education, respectively. The output of this research can be used for policy makers to start providing support on policies, infrastructures and social innovations on the most affected dimensions in order to reduce the impact of this pandemic on citizens’ everyday life and their quality of life. Also using fuzzy TOPSIS in recognizing the most affected dimensions of quality of life of citizens is a theoretical implication of this research for similar ideas of future researchers. This study is a pioneer in investigating the effects of COVID-19 pandemic on dimensions of life quality of citizens. Also linking the better life index, as a comprehensive index, which has a direct impact on people’s lives to social innovation is another novelty of this research. As it opens a new window for social innovators to know how they can use their innovation capacity to have higher impact on society by shedding light on the main challenges occurred in people’s lives. In this research we have decided to use primary data on perceptions of citizens as waiting to get the official secondary data might take long and, on that time, we might be deep in these societal problems and it might be late to make new directions on them. Research paper Keywords: Social innovation; Better life index; OECD; Fuzzy TOPSIS; Iran; COVID-19 Reference to this paper should be made as follows: Sharafi Farzad, F., Salamzadeh, Y., Bin Amran, A., & Hafezalkotob, A. (2020). Social Innovation: Towards a Better Life after COVID-19 Crisis: What to Concentrate On, Journal of Entrepreneurship, Business and Economics , 8 (1), 89–120.